The Impact of Tax Incentives on the Economic Activity of Entrepreneurs - Jarkko Harju; Tuomas Kosonen (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies the effect of Finnish tax reforms in the mid 1990s on the economic activity and tax avoidance decisions of the owners of small businesses. The reforms reduced income tax rates and increased tax planning incentives for small business owners. They applied only to unincorporated firms. We utilize both a theoretical model and empirical data. The empirical strategy is to use the reforms as a natural experiment to estimate the causal impact of the reforms. The results imply that entrepreneurs react to tax incentives along both real and avoidance margins, while the latter elasticity is larger.
Keywords: H25; H24; H22; 330; entrepreneurs; small businesses; tax incidence